Networks: Supramolecular Nanofiber Webs in Nonwoven Scaffolds as Potential Filter Media (Small 12/2013). Issue 12 (14th June 2013) - Misslitz, Holger; Kreger, Klaus; Schmidt, Hans‐Werner
<x xml:space="preserve">Abstract</x> Typically, polymer micro‐ and nanofibers are prepared by top‐down approaches such as meltblowing or electrospinning. In contrast, H.‐W. Schmidt and co‐workers demonstrate on page 2053 a bottom‐up approach via the self‐assembly of small molecules to supramolecular nanofibers. This approach can form supramolecular nanofiber webs within a scaffold in situ. The remarkable intrinsic stability of the supramolecular nanofibers in combination with their good adhesion on the polymer scaffold result in microfiber/nanofiber composites, which are stable under typical air filtration conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>